2021
DOI: 10.1097/rlu.0000000000003394
|View full text |Cite
|
Sign up to set email alerts
|

68Ga–Prostate-Specific Membrane Antigen PET/CT Uptake in Intraventricular Meningioma in the Choroid Plexus

Abstract: A 68-year-old man in whom a prostate cancer biochemical recurrence was being investigated was referred for a full-body 68Ga–prostate-specific membrane antigen PET/CT. Focal uptake in a lesion on the choroid plexus projection was detected. Patient had no neurological complaints. A previous MRI performed 4 years ago showed the same lesion. According to the location and radiological and clinical characteristics, the diagnosis of meningioma was defined. The interpretation of prostate-specific membrane antigen PET/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Primary intraosseous meningioma should be differentiated from osteosarcoma, 4 Ewing sarcoma, 5 metastases, 6 and xanthomas 7 . Many studies suggested that meningioma can cause increased uptake of various radiotracers, including 18 F-FDG, 3 68 Ga-DOTATATE, 8 68 Ga-PSMA, 9 18 F-FLT, 10 18 F-florapronol, 11 and so on. 68 Ga-labeled FAPI has recently been introduced as a promising tumor imaging agent, which has shown promising results in the diagnosis of cancer and inflammatory diseases 12–14 .…”
mentioning
confidence: 99%
“…Primary intraosseous meningioma should be differentiated from osteosarcoma, 4 Ewing sarcoma, 5 metastases, 6 and xanthomas 7 . Many studies suggested that meningioma can cause increased uptake of various radiotracers, including 18 F-FDG, 3 68 Ga-DOTATATE, 8 68 Ga-PSMA, 9 18 F-FLT, 10 18 F-florapronol, 11 and so on. 68 Ga-labeled FAPI has recently been introduced as a promising tumor imaging agent, which has shown promising results in the diagnosis of cancer and inflammatory diseases 12–14 .…”
mentioning
confidence: 99%
“…In routine PSMA imaging, normal brain parenchyma does not demonstrate significant PSMA uptake which provides a suitable background and contributes to the sensitivity for the detection of these various brain pathologies. 17 , 20 Our case report adds to the existing literature of cases of meningioma showing 68 Ga-PSMA uptake [ [21] , [22] , [23] , [24] ].…”
Section: Discussionmentioning
confidence: 62%
“…3,4 There are also several reports demonstrating 68 Ga-PSMA uptake in meningiomas on PSMA-targeted PET/CT. [5][6][7][8] However, to the best of our knowledge, this is the first report demonstrating the progression of 68 Ga-PSMA uptake in cranial meningioma by PET/CT imaging in a patient receiving hormone therapy. PET/CT images (D-E) obtained after RT (54 Gy, 1.8 Gy per fraction) administered to this lesion in the interval period revealed a partial regression of PSMA expression.…”
mentioning
confidence: 95%
“…In the literature, it has been reported that meningiomas may contain hormone receptors such as gonadotropin-releasing hormone or progesterone, and therefore these lesions may enlarge in patients treated with LH-RH agonist 3,4. There are also several reports demonstrating 68 Ga-PSMA uptake in meningiomas on PSMA-targeted PET/CT [5][6][7][8]. However, to the best of our knowledge, this is the first report demonstrating the progression of 68 Ga-PSMA uptake in cranial meningioma by PET/CT imaging in a patient receiving hormone therapy.…”
mentioning
confidence: 99%